Histological study of photoreceptor cells in retina of Rana ridibunda ridibunda pallas eye and the effect of exposure to some wavelengths of visible light - hamd Jundary Jumea; Khalida Nayef Mustafa (College of Education for Pure Sciences, 2010)
Abstract The present study comprised the histological structure of the retina, especially the pigment epitheiium and photoreceptor cells, in the eye of the frog Rana ridibunda ridibunda pallas. On the other hand the study include the effect of exposure to three different wave lengths of the visible light (blue, green and yellow) at 510,525,580 nm of at wave lengths and light intensity, 20,80,100 lux respetively on the pigment epithelium and photoreceptor cells of the retina. The time of exposure was ten continuos weeks. The results revealed that the retina of the frog emposed of eight layers & two membranes as that of the other vertebrates. The pigment epithelium arranged as the row of columnar cells which separate the choroids and retina. The photoreceptor cell layer composed of rods and cones. Two types of rods appeared which were adominant red rods and green rods as in some other amphibia. There were two types of cones which were double & single cones which consist of oil droplet at the apex of ellipsoid portions. The results of light exposure revealed that the blue light injuries appeared after one week which were adecrease in melanin granules and increase in phagosomes as well as the injuried of outer segments of photoreceptor cells. The injuried increased as the time of exposure prolonged. After seven weeks the injuries were rod outer segments shortening, cone thining,rod myoid pyknosis and swelling of nuclei of some cones. After ten weeks of exposure awide damage appeared in the pigment epithelium and photoreceptor cells, and phagocytes appeared in the location of damage and the nuclei degenerated and necroted. The exposure to green and yellow light also incluced injuries in the pigment epithelium layer and photoreceptor cells layer, some similar to that of the blue light but less acute. On the other hand the injuries of green light more sever than that of the yellow light.